2016
DOI: 10.1177/0047287515626304
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Panel Data Analysis of Climate and Tourism Demand

Abstract: A new model that links climate and seasonal tourism demand is developed to study the effects of home climate, destination climate, and climate difference between destinations and source markets on seasonal tourism demand. Using the dynamic panel data technique, the study focuses on the demand of tourists from Hong Kong for 19 of the major tourism cities in Mainland China. The results show that the home climate, destination climate, and the difference in climate between home and destination cities all have sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 69 publications
(95 reference statements)
2
57
0
3
Order By: Relevance
“…Last, system GMM estimator can improve the efficiency and finite-sample properties. This estimator has been widely applied in tourism related studies (e.g., Balli, Balli, & Louis, 2016;Etzo, Massidda, & Piras, 2014;Li, Song, & Li, 2017).…”
Section: Estimator: System Gmmmentioning
confidence: 99%
“…Last, system GMM estimator can improve the efficiency and finite-sample properties. This estimator has been widely applied in tourism related studies (e.g., Balli, Balli, & Louis, 2016;Etzo, Massidda, & Piras, 2014;Li, Song, & Li, 2017).…”
Section: Estimator: System Gmmmentioning
confidence: 99%
“…For tourists, a benevolent climate is one of the main attractions for many destinations. Empirical studies have identified various climaterelated attributes influencing tourists' travel decisions (Hamilton & Lau, 2006;Law & Cheung, 2007;Li, Song, & Li, 2017;Rosselló-Nadal, Riera-Font, & Cárdenas, 2011). Among these attributes, air quality is particularly interesting for policymakers, because it can be controlled to some extent through regulations or incentives to decrease air pollutant emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Otro elemento clave respecto del factor clima, es el tiempo de ocio, entendidos como determinantes de la elección de un destino de viaje, juicio que es compartido por otros estudios, confirmando que el clima no únicamente influye en la decisión de viajar a un destino en particular (Li, et al, 2017), sino que también es un factor clave que afecta la experiencia de viaje y, por consiguiente, determina la intención de repetir la visita en posteriores ocasiones. Es así como Wilson y Becken, 2011, encontraron además que la gente de países muy calurosos o muy fríos viajan más, al tiempo que, los países tropicales, son los que atraen a más turistas.…”
Section: Revisión De La Literaturaunclassified